2012
DOI: 10.1111/j.1651-2227.2012.02797.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the transcutaneous bilirubinometers BiliCheck and Minolta JM‐103 in preterm neonates

Abstract: TcB determined with JM-103 gave values much lower than those obtained with BiliCheck. The underestimation of TsB increased with increasing concentrations. By using transcutaneous bilirubinometers in preterm neonates, 24-36% of the blood samples could be saved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Pearson’s correlation coefficient obtained with Bilistick (r = 0.961) was higher than those reported for any transcutaneous POC instrument that ranged from 0.70 to 0.87 [13,14,15,16,17,18,19,20,21]. The Bland-Altman analysis showed a mean difference between hospital laboratory results and Bilistick determinations of 10.3 µmol/l and a 95% confidence interval of –38.0 to –58.7 µmol/l.…”
Section: Discussionmentioning
confidence: 89%
“…Pearson’s correlation coefficient obtained with Bilistick (r = 0.961) was higher than those reported for any transcutaneous POC instrument that ranged from 0.70 to 0.87 [13,14,15,16,17,18,19,20,21]. The Bland-Altman analysis showed a mean difference between hospital laboratory results and Bilistick determinations of 10.3 µmol/l and a 95% confidence interval of –38.0 to –58.7 µmol/l.…”
Section: Discussionmentioning
confidence: 89%
“…Depending on the device and target populations, TcB may either overestimate or underestimate bilirubin level in jaundiced neonates. 12,14,15 TcB screening in early hours of life may be a useful marker to foretell the possibility of hyperbilirubinemia in later days of life. 12,[16][17][18][19] In the present study, we showed that TSB and sternum TcB levels were plausibly correlated with each other in full term and near term infants with hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are controversies between the various studies about the value and use of BiliChek in premature infants. Ebbesen et al (2012) found that BiliChek is suitable for screening in both NICU and healthy newborn infants with jaundice, with regarding the need for phototherapy (6), and Willems et al (2004) showed that the BiliChek application in the NICU environment has the potential to reduce the number of blood samples taken by 40% (7). However, several studies have provided results for correlation coefficients between TCB and TSB, and the pooled estimates, according to the site of measurement, were 0.35 -0.65 with 95% confidence interval.…”
Section: Introductionmentioning
confidence: 99%